10z-4=6+10z

Simple and best practice solution for 10z-4=6+10z equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 10z-4=6+10z equation:



10z-4=6+10z
We move all terms to the left:
10z-4-(6+10z)=0
We add all the numbers together, and all the variables
10z-(10z+6)-4=0
We get rid of parentheses
10z-10z-6-4=0
We add all the numbers together, and all the variables
-10!=0
There is no solution for this equation

See similar equations:

| -8(1÷6r)-3r=-416 | | |7-x|+4=2x+5 | | 10f+6(f-7=18 | | 2v-5=8v=11 | | -6k-12=78 | | 36=11x+75–8x | | 7n^2-5n-78=0 | | 21x+26x=90 | | -5.5-4x-3.8-2x=-5x+1.5 | | -5(-6x+3)=-15+30x | | 13x+6=-6 | | u/3-8=1 | | -x2-25=0 | | 6y+10y=12y | | 62=8x+22 | | 2(x+2)=7(2+x) | | 56-4x=28 | | 11(3+2x)=0 | | 2y=4(2.5)/ | | 7n+4-12n=4n+7-8n | | 2x-1=x+11 | | -2m+6=-(4+2m) | | -7+v/3=-25 | | 76x+32=48x+256 | | 7j+10=-6+3j | | 25x+350=35x+200 | | 10=3p+4-2p | | -15+m/6=57 | | 5(v-1)=2v+6-3(-3v-1) | | 4+2(b+3)=0 | | -7x2-29x-49=0 | | 2y=4(2.5) |

Equations solver categories